Ọsẹ Dúdú: Exploring the Benefits of Yoruba Indigenous Black Soap in Southwest, Nigeria - Adewusi, Adedeji Oluwaseun; Akanle, Olayinka (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
This study explored the benefits of the production, sale, and consumption of Indigenous black soap (ọsẹ dúdú) in southwest Nigeria. A multistage sampling technique was used to select 71 participants from Oyo, Ogun, and Lagos states. Participants were extensively interviewed, and their responses were analyzed and placed into themes. The study found certain economic- and health-related benefits attached to the production, sale, and consumption of black soap. These benefits could help drive sustainable development in Indigenous communities in Nigeria and the model could be used in Indigenous communities in other countries. Ọsẹ dúdú was also a major ingredient, in conjunction with other herbs, in medicines that were perceived to have important health benefits. Policy recommendations are suggested.